Indonesian Maritime Law Enforcement: Progress and Problems - Abraham, Andre (UI Scholars Hub, 2017)
Indonesia as maritime country may face difficulties in law enforcement at sea. The broad variety of problems and challenges can be found on Indonesia waters, included coastal area and the sea itself. Indonesia has been involved on making maritime law since UNCLOS 1982, with archipelagic state concept that gave significant implication to the law of the sea. Times change, the problem that occurred at sea could be different. Maritime law enforcement would be challenged to be adaptable for the new problems and how Indonesia develop its maritime law to face new challenges.